1984
DOI: 10.1090/s0025-5718-1984-0725999-4
|View full text |Cite
|
Sign up to set email alerts
|

Odd triperfect numbers

Abstract: Abstract. We prove that an odd triperfect number has at least ten distinct prime factors. The following lemmas are easy to prove:Lemma l.IfNisOT,(1) a/s are even for 1 < I < r.Lemma 2. // TV is OT and q is a prime factor of a(pf-) for some i, then q = 3 or q = pj for some j, 1 ^ y < r.Lemma 3. If N is OT and r = 9, ps < 80.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Hence 5 5 1 a(p^) or 5 5 6 . In (1), 3 2 + a(7 fl3 ), 3 + a(13 a '), 3 + a(19 a ')> 3 + a(31" 8 ) because 371 a(7 8 ), 611 <T(13 2 ), 1271 a(19 2 ), and 3311 a(31 2 ).…”
Section: The Case 17 + Nmentioning
confidence: 98%
See 3 more Smart Citations
“…Hence 5 5 1 a(p^) or 5 5 6 . In (1), 3 2 + a(7 fl3 ), 3 + a(13 a '), 3 + a(19 a ')> 3 + a(31" 8 ) because 371 a(7 8 ), 611 <T(13 2 ), 1271 a(19 2 ), and 3311 a(31 2 ).…”
Section: The Case 17 + Nmentioning
confidence: 98%
“…Since 829|a(5 8 ), we have 5 8 tt N by Lemma 1. Suppose that 5 6 \\N. Then p 10 = 19531 because a(5 6 ) = 19531.…”
Section: The Case 171nmentioning
confidence: 99%
See 2 more Smart Citations
“…McDaniel [4] and Cohen [2] proved that an OT number has at least nine distinct prime factors; the author proved that it has at least ten prime factors [3], and Beck and Najar [1] showed that it exceeds 1050.…”
mentioning
confidence: 99%